Advanced Airway Management in a Pediatric Patient with Apert Syndrome - Combined Use of McGrath® Mac Videolaryngoscope and Fiberoptic Bronchoscope - Praveen Ramasamy (JK Science)
Apert syndrome is a rare genetic disorder that poses significant challenges for airway management due to craniofacial abnormalities. This case report describes a successful intubation in a paediatric patient using a combined approach. The McGrath® video laryngoscope provided better glottic visualization than a conventional laryngoscope but posed challenges due to its curvature. To overcome this, a fiberoptic bronchoscope was used as a stylet, allowing precise tube placement. This method proved effective in managing the difficult airway, emphasizing the importance of individualized strategies for intubation in children with craniofacial anomalies.